Performance Analysis of MFCC and LPCC Techniques in Automatic Speech Recognition (International Journal of Engineering and Computer Science, 2014)
As a result of ample development of computers, the various types of information exchange between man and computer are discovered. At present, inputting the data in computer by speech and converting the data into the another form for eg. Text. with the help of automatic speech recognition system  and its recognition by the computer is one of the developed scientific fields. As each language has its specific feature, the various speech recognition systems are investigated for the different languages. In this paper, we have taken two algorithms known as MFCC and LPCC. These two algorithms are used for feature extraction. The performances of the two algorithms are compared to achieve better performance with high recognition rate and low computational complexity and the major advantage of comparing these two algorithms is that they improves the reliability of the system.